Cost Analysis of Premixed Multichamber Bags versus Compounded Parenteral Nutrition: Breakeven Point. Issue 2 (February 2014) - Bozat, Erkut; Korubuk, Gamze; Onar, Pelin; Abbasoglu, Osman
Background: Industrially premixed multichamber bags or hospital-manufactured compounded products can be used for parenteral nutrition. The aim of this study was to compare the cost of these 2 approaches. Materials and Methods: Costs of compounded parenteral nutrition bags in an university hospital were calculated. A total of 600 bags that were administered during 34 days between December 10, 2009 and February 17, 2010 were included in the analysis. For quality control, specific gravity evaluation of the filled bags was performed. Results: It was calculated that the variable cost of a hospital compounded bag was $26.15. If we take the annual fixed costs into consideration, the production cost reaches $36.09 for each unit. It was estimated that the cost for the corresponding multichamber bag was $37.79. Taking the fixed and the variable costs into account, the breakeven point of the hospital compounded and the premixed multichamber bags was seen at 5, 404 units per year. In specific gravity evaluation, it was observed that the mean and interval values were inside the upper and lower control margins. Conclusion: In this analysis, usage of hospital-compounded parenteral nutrition bags showed a cost advantage in hospitals that treat more than 15 patients per day. In small volume hospitals, premixed multichamber bags may be more beneficial.